PENGARUH MODEL KOOPERATIF TIPE THINK-PAIR-SHARE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA MTs. AL-MADANI PONTIANAK - Wahyuni, Nurfita; Mirza, Ade; Ahmad B, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to know the effect of Think-Pair-Share (TPS) type of cooperative learning model on students’ mathematical communication ability in function and relation subject. The research method was pre-experimental and research design was One Shot Case Study. The subject of this research was students of 8th grade of MTs TI Al-Madani Pontianak. The sample of this research was VIII B. The result of data analysis using One Sample T test showed that there was no positive effect on students’ mathematical communication ability that have been given by Think-Pair-Share (TPS) type of cooperative learning model. The conclusion was Think-Pair-Share (TPS) type of cooperative learning model couldn’t be used to increase students’ mathematical communication ability in students of 8th grade of MTs TI Al-Madani Pontianak. This is proved by the average mathematical communication ability score of the students in Think-Pair-Share (TPS) type of cooperative learning model which is 6.94 of the highest score. Keyword: communication, ability, think-pair-share learning, model